Globalization Versus Localization – Economic Development Perspectives - Jovanova, Kristina (European Journal of Sustainable Development, 2017)
Economic globalization leads to extreme development imbalances and represents a cause for the growing inequality between the centre and the periphery on the global economic map. It is in collision with the social protection system, a public good that can be provided for by political process only. The capital is untying the national boundaries and starts serving its own purposes, entailing transformation of the territorial (national) state into a market corporate state. By opening the financial channels for credit indebtedness, the speculative capital is enthroned on the top of the capitalist order and takes dominant role in the new era of global mega capitalism, with a purpose of cleaning the road to its full domination, preparing the world for the new Kondratieff technological cycle. Information, knowledge and technological innovations are driving forces to the global-local networking and the future of the economic development is the sustainable cooperation and synergies between central and local governments and between global and local businesses with an aim of redirecting the economic systems from unsustainable to self-functional. The contemporary determinants to the economic sustainability are based on the creation and use of knowledge in the economic processes. Keywords: economic globalization, megacapitalism, economic localization, technology, innovations, Knowlegd Based Economy